A Brief Description on Fibonacci Series (International Journal of Innovative Research in Engineering & Management, 2021)
The Fibonacci arrangements of numbers as well as the related  "Golden Ratio" shown in nature and certain masterpieces.  This paper aims to prove that the “Power of Math” can be  found with “Fibonacci Numbers”. Fibonacci can be found in  nature in the renowned bunny explore as well as in lovely  blossoms. On the highest point of sunflower and seeds are  squeezed in light of a particular objective so they track the  case of Fibonacci plan. Since Fibonacci numbers has a main  role in any individual’s day-to-day life. One can see that a  large number of regular things that follows Fibonacci  succession. Apparently in natural situations like expanding in  plants, phyllotaxis i.e., the way of arrangement of leaves, and  organic thing fledglings of uncurling plant, and the game  design of pinecone's bracts, and so on. At present Fibonacci  numbers assumes a vital part in the coding hypothesis.  Fibonacci numbers are in various structures and broadly  applicable in developing security coding. The Fibonacci series  can be used in improving the security of communication in the  future.
Keywords: Fibonacci Numbers; Golden Ratio; Nature; Series; Sequence